2014
DOI: 10.1002/gcc.22197
|View full text |Cite
|
Sign up to set email alerts
|

Promoter‐specific alterations of APC are a rare cause for mutation‐negative familial adenomatous polyposis

Abstract: n familial adenomatous polyposis (FAP), 20% of classical and 70% of attenuated/atypical (AFAP) cases remain mutation-negative after routine testing; yet, allelic expression imbalance may suggest an APC alteration. Our aim was to determine the proportion of families attributable to genetic or epigenetic changes in the APC promoter region. We studied 51 unrelated families/cases (26 with classical FAP and 25 with AFAP) with no point mutations in the exons and exon/intron borders and no rearrangements by multiplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 18 publications
(36 reference statements)
5
37
1
1
Order By: Relevance
“…The families were associated with ASE imbalance of APC by SNuPE but no identifiable causative change in APC had been detected by PTT, Sanger sequencing of all exons and intron/exon borders, MLPA, and promoter mutation and methylation analyses (ref. [8] and this study). Only family 85 included several affected members.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The families were associated with ASE imbalance of APC by SNuPE but no identifiable causative change in APC had been detected by PTT, Sanger sequencing of all exons and intron/exon borders, MLPA, and promoter mutation and methylation analyses (ref. [8] and this study). Only family 85 included several affected members.…”
Section: Resultssupporting
confidence: 62%
“…This is likely attributable to some commonly observed disadvantages of PTT, such as decreased RNA stability and assay artifacts [24]. Instead of PTT, family 163 originally underwent an exon-by-exon screen in genomic DNA [8] that, obviously, was not able to capture deep intronic mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although methylation caused the loosing of 1A isoform mRNA and a reduction in total APC transcript levels, APC gene expression was retained from promoter 1B [83] . Moreover, a recent study of Pavicic demonstrated that promoter 1B deletions of APC are not very common [84] . Thus, all these studies imply that > T were determined as associated with the FCCTX phenotype [61] .…”
Section: Familial Crc Type Xmentioning
confidence: 99%
“…Germline MMR gene mutations -Lindor et al [51] Klarskov et al [52] Sánchez-Tomé et al [53] Tumor supressor gene loci loss APC mutations 77% Francisco et al [56] KRAS mutations 46% Francisco et al [56] MGMT methylation 36% Francisco et al [56] Chromosome gains 20q, 19 and 17 Therkildsen et al [57] Chromosome loss 8p, 15, 18 Therkildsen et al [57] Signaling by G protein coupled receptor up-regulated Dominguez-Valentin et al [58] ( even though APC promoter methylation occurs in early during colon neoplasia progression, it does not result in complete gene inactivation or act as a "second hit" [84] and promoter-specific alterations of APC rarely leads to mutation-negative FAP [84] . In addition to APC, hypermethylation of other genes are usually observed in both FAP-related and sporadic duodenal carcinomas [85] .…”
Section: Molecular Features Refmentioning
confidence: 99%